2008
DOI: 10.1021/es801792z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated House Dust and Serum Concentrations of PBDEs in California: Unintended Consequences of Furniture Flammability Standards?

Abstract: Studies show higher house dust and body burden levels of PBDE flame retardants in North America than Europe; but little is known about exposure variation within North America, where California’s furniture flammability standard affects PBDE use. We compared dust samples from 49 homes in two California communities with 120 Massachusetts homes and with other published studies. Dust concentrations [median (range) ng/g] in California homes of BDE-47, -99, and -100 were 2700 (112-107 000), 3800 (102-170 000), and 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
206
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(229 citation statements)
references
References 30 publications
16
206
7
Order By: Relevance
“…Several investigators have observed that biological PBDE levels measured in various populations mirror the global patterns in PBDE dust concentrations (Sjodin et al, 2008;Zota et al, 2008;Harrad et al, 2008b). Indeed, it is likely that the relatively high levels of PBDEs measured in blood and breast milk from North Americans compared with Europeans are the result of higher concentrations of PBDEs in North American household dust (Frederiksen et al, 2009).…”
Section: Importance Of Residential Dust As a Source Of Pbde Exposurementioning
confidence: 98%
See 3 more Smart Citations
“…Several investigators have observed that biological PBDE levels measured in various populations mirror the global patterns in PBDE dust concentrations (Sjodin et al, 2008;Zota et al, 2008;Harrad et al, 2008b). Indeed, it is likely that the relatively high levels of PBDEs measured in blood and breast milk from North Americans compared with Europeans are the result of higher concentrations of PBDEs in North American household dust (Frederiksen et al, 2009).…”
Section: Importance Of Residential Dust As a Source Of Pbde Exposurementioning
confidence: 98%
“…Similarly, de Wit et al (2008) reported that median dust concentrations of BDE-209 were higher in apartments than in houses. In addition, Zota et al (2008) found that residential dust collected from households in a low-income community in California had higher PBDE levels than dust from a more affluent California community.…”
Section: Determinants Of Pbde Levels In Residential Dustmentioning
confidence: 99%
See 2 more Smart Citations
“…An unintended consequence of California's Technical Bulletin 117 (TB 117)-a fire safety law promulgated in the 1970s which requires that furniture, baby, and other household products resist open flame (California Department of Consumer Affairs 2000; Zota et al 2008)-is that PBDE concentrations in California children are now among the highest measured worldwide . Until 2005, the predominant chemical flame retardant used to comply with TB 117 was pentaBDE (comprising congeners BDEs 47, 99, 100, and 153).…”
mentioning
confidence: 99%